Preparation and Characterization of Nickel Oxide Thin Films: A review - Ho, Soon Min (Research India Publications, 2016)
Abundant literature is available on the preparation and characterization of metal oxide films as described by many researchers. Generally, physical and chemical deposition techniques could be used to prepare NiO films on various substrates. The obtained films will be studied using different tools such as xray diffraction, scanning electron microscopy and UV-Visible spectrophotometer in order to determine the best experimental conditions.